Detekce invazivní aspergilózy pomocí PCR a real-time PCR--prednosti a úskalí - Lengerová, Martina; Rácil, Zdenek; Hrncírová, Kristýna; Volfová, Pavlína; Lochmanová, Jana; Dvoráková, Dana; Mayer, Jirí (Klinicka mikrobiologie a infekcni lekarstvi, 2007)
PCR detection of fungal pathogens in clinical samples has been discussed in journals for more than two decades. However, its use for diagnosing invasive aspergillosis is still controversial, despite the fact that molecular methods are routinely used in various fields of modern microbiology. These are e. g. genotyping of bacterial strains resistant to antibiotics, molecular epidemiology or routine detection of viral infections in clinical material. PCR methods have made the diagnostic applications faster, simpler and more accurate. This review deals with issues related to molecular methods for diagnosing invasive fungal infections and the main factors limiting their use in everyday clinical practice.
Keywords: senzitivita a specificita; Aspergillus; DNA fungální; Aspergillosis; polymerázová řetězová reakce; DNA, Fungal; Polymerase Chain Reaction; lidé; Humans; aspergilóza; Sensitivity and Specificity